2013
DOI: 10.1371/journal.pone.0063878
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Increases Secretion of Rat Submandibular Gland via Adiponectin Receptors-Mediated AMPK Signaling

Abstract: Adiponectin and adiponectin receptors (AdipoR1/2) are expressed in various tissues and are involved in the regulation of multiple functions such as energy metabolism and inflammatory responses. However, the effect of adiponectin and AdipoRs in submandibular glands has not been fully evaluated. In the present study, we found that mRNA and protein of both adiponectin and AdipoR1/2 were expressed in rat submandibular glands and in the SMG-C6 cell line, as evidenced by RT-PCR and Western blot analysis. Immunofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…In addition, AdipoR1/2 mRNA has been detected in cultured human minor salivary gland epithelial cells (Katsiougiannis et al , ) and mouse embryos SMG (Zhou et al , ). Our recent study has shown that adiponectin and AdipoRs are expressed in rat SMG (Ding et al , ). In the present study, we provided further evidence that adiponectin and AdipoRs were expressed in both mouse and human SMGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AdipoR1/2 mRNA has been detected in cultured human minor salivary gland epithelial cells (Katsiougiannis et al , ) and mouse embryos SMG (Zhou et al , ). Our recent study has shown that adiponectin and AdipoRs are expressed in rat SMG (Ding et al , ). In the present study, we provided further evidence that adiponectin and AdipoRs were expressed in both mouse and human SMGs.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that submandibular gland (SMG), which is structurally and functionally different from minor salivary gland, is the main resource of saliva under resting state (Langdon, ). Our laboratory recently found that adiponectin was expressed in rat SMG and adiponectin acted as a promoter of saliva secretion in isolated SMG (Ding et al , ). However, the possible role of adiponectin in SMG under pathological state is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the presence of mild chronic gingival inflammation before tooth‐cleaning, which had resolved by day 14, and is similar to the changes described in people . Mechanisms involved in increased salivary adiponectin concentrations in the presence of chronic gingivitis would include (1) increased permeability of regional blood vessels due to localized periodontitis or gingivitis, leading to adiponectin leakage from the blood, or (2) increased local production of salivary adiponectin from a damaged gingiva, as a reaction of regulating local inflammation . Further studies should now be considered to elucidate the pathogenesis of increased salivary adiponectin in dogs with acute gingival inflammation.…”
Section: Adiponectin Concentrations (Ng/ml) In Canine Saliva Determinmentioning
confidence: 59%
“…Ding et al (2013) 10 described perfusion of isolated salivary glands with adiponectin which stimulated saliva secretion. Therefore we investigated if a high fat diet could modify the levels of adiponectin in submandibular gland.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Thus receptors present in salivary glands might be involved in the effects of metabolic changes regulation such as local inflammatory and immunological processes. 10 The consumption of high caloric palatable foods has increased significantly in recent decades leading obesity to achieve epidemic proportions with negative impacts for the economy and general health worldwide. 11,12 Therefore understanding the pathophysiology mechanism involved in the development of obesity and its related diseases has become timely.…”
Section: Introductionmentioning
confidence: 99%